2011
DOI: 10.1007/s12038-011-9098-x
|View full text |Cite
|
Sign up to set email alerts
|

Transgene transmission in chickens by sperm-mediated gene transfer after seminal plasma removal and exogenous DNA treated with dimethylsulfoxide or N,N-dimethylacetamide

Abstract: Transgenic animals have been successfully produced by mass gene transfer techniques such as sperm-mediated gene transfer (SMGT). The aim of this work was to demonstrate transgene transmission by SMGT in chickens using dimethylsulfoxide (DMSO) or N,N-dimethylacetamide (DMAc) as transfectants after seminal plasma removal to prevent DNase activity. Sperm samples were prepared by repetitive washes, and after each wash sperm motility, seminal plasma proteins, exogenous DNA integrity and its uptake by spermatozoa we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…On the other hand, intracellular cryoprotectants such as DMSO can improve DNA uptake by sperm cells as previously demonstrated in rabbits, mice and chicken Shen et al, 2006, Collares et a., 2011. Therefore other intracellular cryoprotectants such as N, N-dimetylacetamide (DMA) that have been used recently in boar sperm cryopresenvation (Bianchi et al, 2008) could also be used to increase the uptake of exogenous DNA by spermatozoa as demonstrated for chickens (Collares et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, intracellular cryoprotectants such as DMSO can improve DNA uptake by sperm cells as previously demonstrated in rabbits, mice and chicken Shen et al, 2006, Collares et a., 2011. Therefore other intracellular cryoprotectants such as N, N-dimetylacetamide (DMA) that have been used recently in boar sperm cryopresenvation (Bianchi et al, 2008) could also be used to increase the uptake of exogenous DNA by spermatozoa as demonstrated for chickens (Collares et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Therefore other intracellular cryoprotectants such as N, N-dimetylacetamide (DMA) that have been used recently in boar sperm cryopresenvation (Bianchi et al, 2008) could also be used to increase the uptake of exogenous DNA by spermatozoa as demonstrated for chickens (Collares et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In this method the transgene containing the shRNA is attached or inserted into the sperm head and then used to fertilise eggs (Moreira et al 2007). DNA can be introduce to the sperm head in several ways including transfection (Collares et al 2011), attachment by antibodies (Chang et al 2002) and disruption by repeated freeze-thaw cycles or exposure to detergents (Perry et al 2001). Random insertion of the shRNA construct into the genome can lead to problems including overloading of the RNAi machinery (Grimm et al 2006), complete elimination of a required gene product, or epigenetic silencing of the construct.…”
Section: Transgenic Expression Of Rnai-inducing Moleculesmentioning
confidence: 99%
“…El-Gendy et al [12] successfully developed the F 1 transgenic chickens by SMGT and using lipofectin as a transfection reagent. Also, Collares et al [36] reported successful transmission of an exogenous DNA to chickens by SMGT after removing seminal plasma and treating the exogenous DNA with dimethylsulfoxide or N,Ndimethylacetamide. Lubart et al [37] indicated that there is an accelerated exchange and uptake of Ca 2+ between the medium and the bovine sperm cells during irradiation with 6-8 J/cm 2 He-Ne (633 nm).…”
Section: Figmentioning
confidence: 99%